Community water fluoridation and its influence on periodontal health in different age groups - Arti Dixit; Vijaysinh Ramchandra Tanpure; Piyush Jaiswal; Pallavi Tripathi Rameshchandra; Deeksha Shetty; Swastidipa Mandal; Bhumika Kamal Badiyani; Amit Kumar (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: Community water fluoridation is a well-recognized public health initiative known for its efficacy in preventing dental cavities. The positive effects of fluoride on tooth enamel have led to widespread implementation of water fluoridation programs. Materials and Methods: This cross-sectional study involved 1,000 participants from diverse age groups, spanning children, adolescents, adults, and older adults, residing in both fluoridated and non-fluoridated communities. Comprehensive periodontal assessments included measurements of probing depth (PD), clinical attachment level (CAL), and the presence of gingival inflammation. Participants were categorized into “fluoridated” or “non-fluoridated” groups based on their residential history. Results: Fluoridated communities consistently displayed lower mean PDs, CALs, and rates of gingival inflammation across all age groups. Notably, the reduction in PD and CAL reached approximately 0.5 millimeters and 0.3 millimeters, respectively, while the decrease in gingival inflammation ranged from 3% to 5%. Conclusion: This study suggests a potential link between community water fluoridation and enhanced periodontal health, as evidenced by improved PDs, CALs, and reduced gingival inflammation.